Sertifikasi RSPO Terhadap Ekonomi Sosial Lingkungan Petani Sawit Kpud Makmur Jaya: Sertifikasi RSPO Terhadap Ekonomi Sosial Lingkungan Petani Sawit Kpud Makmur Jaya - Mar’i Muhammad Harahap; Anna Kusumawati (JURNAL ILMIAH AGRINECA, 2026)
This study aimed to analyze the impact of the implementation of Roundtable on Sustainable Palm Oil (RSPO) certification on the economic, social, and environmental aspects of oil palm farmers at KPUD Makmur Jaya. A quantitative research method with a survey approach was employed. The population consisted of 770 farmers, and 88 respondents were selected using the Slovin formula through a simple random sampling technique. Primary data were collected through questionnaires and analyzed using validity and reliability tests, followed by simple linear regression analysis. The results indicated that all research instruments were valid and reliable. The regression analysis showed that RSPO certification had a positive and significant effect on the economic, social, and environmental conditions of oil palm farmers. Economically, the certification contributed to increased income, productivity, and market access. Environmentally, it encouraged the adoption of sustainable cultivation practices, improved waste management, and enhanced environmental awareness. Socially, it strengthened farmers’ knowledge, cooperation, and participation in cooperative activities. Overall, RSPO certification has contributed to improving farmers’ welfare while supporting the implementation of sustainable oil palm plantation management.